Uncovering Students' Perceptions of Slido: An Innovative Engagement with Real-Time Interactive Technology in ESP - Ningsih, Fitria (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2023)
The integration of technology in education, particularly in English for Specific Purposes (ESP) courses, has become increasingly important in providing students with effective and engaging language learning experiences. However, traditional teaching methods have long been criticized for their inability to engage students and promote active participation in the learning process. Thus, this study explored the impact of Slido, an interactive platform, on classroom engagement and learning outcomes in an ESP course. The research design employed mixed methods, including a questionnaire to collect data from ESP students. The findings indicated that Slido technology influenced students' perceptions of classroom engagement, motivation, and satisfaction. The interactive features of Slido, such as quizzes, polls, and surveys, fostered immediate feedback and increased student engagement. ESP teachers were encouraged to incorporate interactive technology like Slido to enhance student learning experiences, while students were encouraged to actively participate in such activities. Further research was recommended to investigate the long-term effectiveness of Slido technology, as well as its impact on ESP teachers' practices and professional development. Overall, Slido technology shows the potential in transforming ESP classrooms into interactive and engaging learning environments. It has the potential to revolutionize language learning and provide students with practical language skills for real-world contexts.